Role of the tail in the regulated state of myosin 2 - Jung, HyunSuk (2011)
Myosin 2 from vertebrate smooth muscle or non-muscle sources is in equilibrium between compact, inactive monomers and thick filaments under physiological conditions. In the inactive monomer, the two heads pack compactly together and the long tail is folded into three closely-packed segments that are associated chiefly with one of the heads. The molecular basis of the folding of the tail remains unexplained. Using electron microscopy, we show that compact monomers of smooth muscle myosin 2 have the same structure in both the native state and following specific, intramolecular photo-cross-linking between Cys109 of the regulatory light chain (RLC) and segment 3 of the tail. Non-specific cross-linking between lysine residues of the folded monomer by glutaraldehyde also does not perturb the compact conformation, and stabilises it against unfolding at high ionic strength. Sequence comparisons across phyla and myosin 2 isoforms suggest that folding of the tail is stabilised by ionic interactions between the positively-charged N-terminal sequence of the RLC and a negatively-charged region near the start of tail segment 3, and that phosphorylation of the RLC could perturb these interactions. Our results support the view that interactions between the heads and the distal tail perform a critical role in regulating activity of myosin 2 molecules through stabilising the compact monomer conformation.